Development of A Contextual Virtual Lab Practicum Module on Energy Material for Class IV Primary Students - Astuti, Feni Tri Astuti; Suryandari, Suryandari; Dwi Ariyani, Yusinta; Perdana Sari, Indah (DAS Institute, 2025)
A learning module is one of the teaching materials that enables students to learn independently so that it is known to what extent pupils understand the learning material. However, teachers still rely on government-printed books to create innovative teaching materials that align with technological advancements. The purpose of this study is to find out if it is possible and how teachers and students would react to making a contextual virtual lab practical module on energy topics for fourth-grade elementary school students using the Research and Development model and a three-stage modified ADDIE development model that includes the analysis stage, the design stage, and the development stage. This research employs both qualitative and quantitative data analysis techniques. We did research and found that the contextual virtual lab practicum module on energy material for SDS IT Bina Anak Islam Krapyak class IV A students can be used for learning activities. This is proven by material expert validation getting an average score of 86% and media expert validation getting an average score of 95%, both of which can be categorized as